Comparison of two different renal access techniques in one-stage percutaneous nephrolithotomy: triangulation versus “eye of the needle” - Salih Budak; Cem Yucel; Erdem Kisa; Zafer Kozacioglu (Annals of Saudi Medicine, 2018)
BACKGROUND: Two primary methods used to create appropriate percutaneous renal access under fluoroscopic guidance are the triangulation technique (TT) and the “eye of the needle” (EN) technique. To the best of our knowledge, no study has yet compared the EN versus TT renal access methods that precede one-stage dilatation during percutaneous nephrolithotomy (PCNL). OBJECTIVES: Compare effects of renal access techniques on the stone-free rate of one-stage PCNL, and the influence on outcomes. DESIGN: Retrospective cross-sectional study. SETTINGS: Tepecik Training and Research Hospital, Turkey. PATIENTS AND METHODS: The records of patients with renal stones larger than 2 cm in diameter who underwent PCNL in our hospital between January 2008 and September 2017 were retrieved. Patients who had undergone one-stage PCNL with the EN renal access technique (EN group) were compared with patients who had undergone one-stage PCNL with the TT renal access technique (TT group). MAIN OUTCOME MEASURES: Operative time, stone size, access location, stone side, length of hospital stay, Hounsfield unit (HU), fluoroscopy time, change in hemoglobin level, complications (modified Clavien classification) and stone-free rate. SAMPLE SIZE: 195. RESULTS: Of 272 records, 195 met inclusion criteria. The one-stage PCNL stone-free rate and other outcomes did not differ significantly between the EN (n=91, 46.7%) and TT groups (n=104, 53.3%). CONCLUSION: According to our study, renal access for one-stage PCNL can be achieved using either the EN or TT technique. The renal access technique used does not independently affect the complication rate. LIMITATIONS: Retrospective, small sample size, and no comparison of body mass index. CONFLICT OF INTEREST: None.